Serum lipid concentration in relation to anthropometric indices of central and peripheral fat distribution in 20,021 British men and women: results from the EPIC-Norfolk population-based cohort study. - Canoy, D; Wareham, N; Luben, R; Welch, A; Bingham, S; Day, N; Khaw, K (2006)
AIMS: Central adiposity has been linked with adverse metabolic profile including dyslipidaemia but recent studies suggested that peripheral fat distribution play a role in regulating daily fluxes in circulating non-esterified fatty acids. We examine whether lipid levels vary between central and peripheral fat distribution in the general population. METHODS AND RESULTS: We examined the cross-sectional relation between fat distribution indices and lipid concentration in 20,021 apparently healthy men and women of the Norfolk cohort of the European Investigation into Cancer and Nutrition (EPIC-Norfolk). Waist-hip ratio was positively related to total and low density lipoprotein (LDL) cholesterol and negatively related to high density lipoprotein (HDL) cholesterol in both men and women, independently of body mass index (BMI). Although similar results were noted for waist circumference, individuals with bigger hip circumference had lower total and LDL-cholesterol and higher HDL-cholesterol when adjusting for BMI and/or waist circumference in both men and women. CONCLUSION: Regional fat distribution was related to lipid profile independently of BMI. The independent contribution of waist and hip circumference in opposite directions was intriguing. These findings may help explain the associations observed between different fat distribution phenotypes and coronary heart disease.